2019
DOI: 10.1016/j.nima.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Study of small-cell 3D silicon pixel detectors for the high luminosity LHC

Abstract: A study of 3D pixel sensors of cell size 50 µm × 50 µm fabricated at IMB-CNM using double-sided n-on-p 3D technology is presented. Sensors were bump-bonded to the ROC4SENS readout chip. For the first time in such a small-pitch hybrid assembly, the sensor response to ionizing radiation in a test beam of 5.6 GeV electrons was studied. Results for non-irradiated sensors are presented, including efficiency, charge sharing, signal-to-noise, and resolution for different incidence angles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In the future, tests with these 3D FE-I4 prototypes at even higher fluences are planned. In parallel, studies with small-pitch 3D pixel sensors connected to the analogue ROC4SENS readout chip with 50×50 µm 2 pixel size are on-going [20]. First results up to 3×10 15 n eq /cm 2 are consistent with this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the future, tests with these 3D FE-I4 prototypes at even higher fluences are planned. In parallel, studies with small-pitch 3D pixel sensors connected to the analogue ROC4SENS readout chip with 50×50 µm 2 pixel size are on-going [20]. First results up to 3×10 15 n eq /cm 2 are consistent with this study.…”
Section: Discussionsupporting
confidence: 82%
“…However, at the time of this study, it has not yet been available. Hence, first small-pitch 3D sensor prototypes have been produced with the option to connect them to the existing FE-I4 and ROC4SENS [20] readout chips.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on 3D technology, which has been demonstrated to be able to work under such extreme conditions [3]. Its main characteristic is the arrangement of electrodes as columns perpendicular to the sensor surface (figure 1).…”
Section: D Pixel Sensors For the Inner Trackermentioning
confidence: 99%
“…3D sensors have already seen use in the insertable barrel pixel layer in the ATLAS inner tracker, and are included in the inner layers of both CMS and ATLAS Phase-II upgrade designs [2,3]. Current research in 3D sensors is focusing on small-cell sensors to meet future requirements for finer granularity in vertexing detectors, and to improve the understanding signal formation and properties for different particle track angles especially in highly-irradiated sensors [17,18,19].…”
Section: D Sensorsmentioning
confidence: 99%
“…a) Left: Schematic cross-section of a small-cell 3D sensor[19], b) right: Hit efficiency as function of bias voltage for an irradiated 3D sensor[17].…”
mentioning
confidence: 99%